RESERVE ASSETS AS SOURCES OF REPLENISHING RESOURCE BASE OF BANKING SECTOR AND IMPROVING ITS STABILITY - Dr. Hadir H Shubbar (Scholar Express Journals, 2023)
The paper focuses on the importance of using reserve assets in order to increase the bank financial stability and the banking system as a whole. The essential requirements for reserving commercial banks have been presented. The methods of regulating the required reserves have been studied. The specific features of applying the required reserves in banking activities (reserve requirements and liquidity, monetary policy, reserve requirements as a monetary tool, reserve requirements as a fiscal tool) have been revealed. The schedule of averaging periods of required reserves for 2019 is being considered. The general principles which credit organizations are guided by when creating reserves are the following: obligatory availability of reserves for all credit organizations throughout their existence; forming reserves in relation to liabilities to legal entities and individuals; possibility of removing from the list obligations for which reserves have been created. It has been mentioned that the main objectives of the reserve requirement system are to provide banks with sufficient liquidity and to regulate the money supply. Particular attention is paid to the Central Bank as a reserve requirements regulator. In accordance with the changes of the Central Bank of July 1, 2019, the established standards on reserve requirements for deposits in national currency are set at 4%, in foreign currency at 14%. Manipulating the required reserve rate will provide the Central Bank with the opportunity to adjust the liquidity and solvency both of an individual bank and the entire banking system. The method of averaging required reserves includes the possibility for a commercial bank not to transfer reserves to the Central Bank based on a certain sum of money. The averaging coefficient is set at 0.25 to the standard volume of required reserves
Keywords: Central Bank; banking system; reserves; requirements